High-performance liquid chromatography of corynomycolic acids as a tool in identification of Corynebacterium species and related organisms. - De Briel, D (1992)
A high-performance liquid chromatography (HPLC) study of 307 strains of Corynebacterium species and related taxa revealed that strains classified as "Corynebacterium aquaticum"; "Corynebacterium asperum"; and Centers for Disease Control (CDC) groups 1, 2, A-3, A-4, A-5, B-1, B-3, E, F-2, and I-2 as well as some unidentified coryneforms do not contain any corynomycolic acids; therefore, they should not be included in the genus Corynebacterium. Such an HPLC method of identification permitted the correct assignment to the genus Rhodococcus of two unpigmented strains of coryneform bacteria whose mycolic acid profiles were comparable to those of Rhodococcus equi. Bacteria belonging to CDC groups ANF-1, ANF-3, F-1, G-1, G-2, and I-1, as well as some other Corynebacterium sp. strains, yielded corynomycolic acid HPLC patterns related to those of Corynebacterium species. Either similarities or differences were observed in the corynomycolic acid profiles of Corynebacterium species tested after culture on sheep blood agar and/or sheep blood agar supplemented with Tween 80, which demonstrated that identification at the species or group level is possible. However, Corynebacterium striatum and CDC group I-1 bacteria as well as CDC group G-1 and group G-2 bacteria had indistinguishable HPLC patterns. Conversely, some variations were observed within some species as Corynebacterium xerosis, C. striatum, and Corynebacterium minutissimum. The evaluation procedure of this HPLC method by mass spectrometry analysis of isolated eluted peaks revealed that analytical reverse-phase HPLC alone does not provide any structural information, since isomers with identical polarities coeluted as a single peak. Nevertheless, HPLC is a rapid and reliable method for identification of corynomycolic acid-containing bacteria in the clinical microbiological laboratory.